A silent voice / vol. 7 - Ōima, Yoshitoki; LeCroy, Steven (2015)
Shoya s life hangs on by a thread after he jumped just in time to save Shoko. Despite the despair, Shoko is determined to move forward and get back what she thinks she has ruined But broken friendships can heal, too. Quietly, but surely, the disbanded crew finds their spirit the show must go on! As the movie-making reconvenes, the kids begin to transform the world that had once been so cruel to them. What could the future hold for everyone?
Reads from right to left.
"A Kodansha Comics Trade Paperback Original"--Colophon.
"T, ages 13+"--Back cover.
Translation of: Koe no katachi.
Keywords: Deaf people -- Fiction; People with disabilities -- Fiction; Bullies and bullying -- Fiction; Conduct of life -- Fiction; Schools -- Fiction; Graphic novels; Deaf children; Bullying; Conduct of life; School children; Teenagers; Comic books, strips, etc; Graphic novels